CONCEPT ECOVILLAGE AS AN ALTERNATIVE SOURCE OF LEARNING GEOGRAPHY - wardana - wibawa (Edusentris, 2021)
ABSTRACT Bandung Regency is one of the regencies in Indonesia where people have high dynamics and mobility. This is marked by the number of developments in various fields. Along with that, increasing population pressure on the environment and of course this situation creates opportunities to increase damage to the environment and the emergence of environmental problems and environmental quality degradation. One of the first steps of the Bandung Regency government is to start making efforts to save the environment. As for the government's efforts in realizing the attitude of caring for the environment by issuing Regulation No. 78 of 2015 concerning the Citarum Movement clean, healthy, beautiful and sustainable. The implementation of the Governor Regulation No. 78 of 2015 is the creation of theEco-Village Village program. District Government Regulations that require the role of students to take part in this program are supported by existing material, namely by the addition of Local Content Materials. Thus, students are expected to play an active role in protecting the environment. This concept can be used as an alternative source of learning in geography subjects in class XI IPS, because in its discussion of the attitude of love for the environment and assessment as well as ways to preserve, control and preserve the environment are discussed in this chapter. The research method, which is used is a qualitative research method with the approach of literature study, comparative study, and object observation. Then combining them with practical activities in adjusting material about the chapter on the love of environment, the analysis in this study was done by comparing the results of observations of objects with literature studies. The results achieved in this study prove that to regulate slum areas can be done by rejuvenation of settlements, through the application of fivecharacteristic concepts ecovillage, so that it is expected to produce settlements that are sustainable and ecological. From the results of the discussion it will be seen that by learning the practices of material suitability and applicability it will be seen in the field. Keywords: Learning Resources, Slums,Ecovillage